Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Evaluate the expression for
g
=
−
1
g = -1
g
=
−
1
.
\newline
Write your answer as a decimal or
whole number
.
\newline
7
+
15.4
g
=
7 + 15.4g =
7
+
15.4
g
=
_____
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate variable expressions involving rational numbers
Full solution
Q.
Evaluate the expression for
g
=
−
1
g = -1
g
=
−
1
.
\newline
Write your answer as a decimal or whole number.
\newline
7
+
15.4
g
=
7 + 15.4g =
7
+
15.4
g
=
_____
Substitute
g
=
−
1
g = -1
g
=
−
1
:
Substitute
g
=
−
1
g = -1
g
=
−
1
into the expression
7
+
15.4
g
7 + 15.4g
7
+
15.4
g
.
\newline
Expression after substitution:
7
+
15.4
(
−
1
)
7 + 15.4(-1)
7
+
15.4
(
−
1
)
Multiply by
−
1
-1
−
1
:
Multiply
15.4
15.4
15.4
by
−
1
-1
−
1
.
15.4
×
−
1
=
−
15.4
15.4 \times -1 = -15.4
15.4
×
−
1
=
−
15.4
Add to
7
7
7
:
Add the result from Step
2
2
2
to
7
7
7
.
\newline
7
+
(
−
15.4
)
=
7
−
15.4
7 + (-15.4) = 7 - 15.4
7
+
(
−
15.4
)
=
7
−
15.4
Calculate the sum:
Calculate the sum.
7
−
15.4
=
−
8.4
7 - 15.4 = -8.4
7
−
15.4
=
−
8.4
More problems from Evaluate variable expressions involving rational numbers
Question
Combine the like terms to create an equivalent expression:
\newline
2
s
+
(
−
4
s
)
=
0
2s+(-4s)=\boxed{\phantom{0}}
2
s
+
(
−
4
s
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
6
p
)
=
□
-4p+(-6p)=\square
−
4
p
+
(
−
6
p
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
4
z
−
(
−
3
z
)
=
□
4z-(-3z)=\square
4
z
−
(
−
3
z
)
=
□
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
r
+
(
−
5
r
)
=
0
r+(-5r)=\boxed{\phantom{0}}
r
+
(
−
5
r
)
=
0
Get tutor help
Posted 1 year ago
Question
Combine the like terms to create an equivalent expression:
\newline
−
4
p
+
(
−
2
)
+
2
p
+
3
=
-4p+(-2)+2p+3=
−
4
p
+
(
−
2
)
+
2
p
+
3
=
Get tutor help
Posted 1 year ago
Question
Rewrite the expression in the form
k
⋅
z
n
k \cdot z^{n}
k
⋅
z
n
.
\newline
Write the exponent as an integer, fraction, or an exact decimal (not a mixed number).
\newline
3
z
4
⋅
3
z
3
4
=
3 \sqrt[4]{z} \cdot 3 z^{\frac{3}{4}}=
3
4
z
⋅
3
z
4
3
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
3
x
y=3^{x}
y
=
3
x
.
\newline
Find
d
2
y
d
x
2
\frac{d^{2} y}{d x^{2}}
d
x
2
d
2
y
\newline
d
2
y
d
x
2
=
\frac{d^{2} y}{d x^{2}}=
d
x
2
d
2
y
=
Get tutor help
Posted 1 year ago
Question
Let
y
=
4
x
2
+
3
x
2
x
−
7
y=\frac{4 x^{2}+3 x}{2 x-7}
y
=
2
x
−
7
4
x
2
+
3
x
.
\newline
d
y
d
x
=
\frac{d y}{d x}=
d
x
d
y
=
Get tutor help
Posted 1 year ago
Question
d
d
x
(
e
x
cos
(
x
)
)
=
\frac{d}{d x}\left(\frac{e^{x}}{\cos (x)}\right)=
d
x
d
(
c
o
s
(
x
)
e
x
)
=
Get tutor help
Posted 9 months ago
Question
Let
f
(
x
)
=
1
x
2
f(x)=\frac{1}{x^{2}}
f
(
x
)
=
x
2
1
.
\newline
f
′
(
5
)
=
f^{\prime}(5)=
f
′
(
5
)
=
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant